Apresentação (Foreword) - Bittar, Marisa (Revista Eletrônica de Educação, 2017)
Presentation of the Commemorative Dossier of the 40 years of the PPGE / UFSCar. Apresentação do Dossiê Comemorativo dos 40 anos do PPGE/UFSCar.